Gestión por procesos y su relación con la comercializacion de insumos agrícolas en la unidad nacional de almacenamiento EP, cantón Quevedo, año 2014. - Aviles Pérez, Angela Cecibel (2016)
This research was conducted in the city of Quevedo and the main objective was to analyze the management of the marketing process of agricultural inputs of National Unity Storage EP Quevedo Canton, Year 2014 interview conducted by the administrator, surveys to employees and enterprise customers are producers of rice crops. Corn, soybeans, bananas etc. Quevedo Canton, whose activity as an institution of the Ecuadorian State contributes effectively to the way agricultural market, through economic activities of storage, management, distribution, and marketing of agricultural inputs. Making their stay in the market. Managers are geared more to the process of marketing of agricultural inputs that are generating returns, in this context storage company UAN-EP, the Canton Quevedo has maintained its portfolio of customers based on the market but with drawbacks due to competition around it, so it is recommended that as a fundamental factor managers are pave the sequential application of administrative functions, as it will allow to act rightly in the management of marketing processes of their products offered in the market and therefore increase customer portfolio. In the course of the investigation, it is possible to identify that farmers are those that promote the circulation of agricultural products, for this reason it must improve marketing of inputs is done and adapt to new realities traditional distribution models to open new markets and introduce technology commercialization process in the area. Keywords: Management, Process, Marketing, Agricultural inputs